2015
DOI: 10.1080/15548627.2015.1117734
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of autophagy by the methyltransferase EZH2 through an MTOR-dependent pathway

Abstract: Macroautophagy is an evolutionarily conserved cellular process involved in the clearance of proteins and organelles. Although the autophagy regulation machinery has been widely studied, the key epigenetic control of autophagy process still remains unknown. Here we report that the methyltransferase EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit) epigenetically represses several negative regulators of the MTOR (mechanistic target of rapamycin [serine/threonine kinase]) pathway, such as TSC2, RHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 61 publications
11
121
0
1
Order By: Relevance
“…T24 cells were seeded in a 96-well plate at a density of 2x10 6 cells per well and cultured with DMSO (5 mM) or methyl jasmonate (0.75, 1.5 and 2.0 mM) for 48 h. Apoptotic rates were assessed using flow cytometry following fluorescein isothiocyanate-conjugated annexin V and propidium iodide staining (BD Pharmingen™ FITC Annexin V; cat. no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…T24 cells were seeded in a 96-well plate at a density of 2x10 6 cells per well and cultured with DMSO (5 mM) or methyl jasmonate (0.75, 1.5 and 2.0 mM) for 48 h. Apoptotic rates were assessed using flow cytometry following fluorescein isothiocyanate-conjugated annexin V and propidium iodide staining (BD Pharmingen™ FITC Annexin V; cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…Enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) is a novel polycomb-group gene identified in Drosophila melanogaster; in 2000, its chromosomal locus was determined to be 7q35 in humans (6). Previous studies revealed that the EZH2 gene participated in cellular growth regulation (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to histone deacetylase inhibitors in non-small cell lung cancer is mediated in part through the activation of nuclear factor-κβ through the phosphatidylinositol 3-kinase/Akt-dependent pathway (41). A number of studies (42)(43)(44) have indicated that the dynamic changes of histone modification may regulate mTOR signaling pathway protein kinase activity. However, the underlying molecular mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…EHMT2/G9a (euchromatic histone lysine methyltransferase 2) [14] and EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit) [15] have both been implicated in autophagy repression under serum starvation by increasing H3K9me2 and H3K27me3 histone mark levels, respectively, of certain autophagy-associated genes. Furthermore, autophagy induction has been demonstrated to affect total H3R17me2, H4K16ac, and H2BK120ub levels through CARM1 (coactivator associated arginine methyltransferase 1) [16], KAT8/hMOF (lysine acetyltransferase 8) [17], and the deubiquitinase USP44 (ubiquitin specific peptidase 44) [18], respectively.…”
Section: Introductionmentioning
confidence: 99%